Present and Preferred Functions of CGCA Members - Brown, Tom (Canadian Journal of Counselling and Psychotherapy, 2012)
This research was undertaken by the CGCA Role Committee as a preliminary step in gathering opinions regarding counsellor role from the membership. A 53-item Counsellor Role Questionnaire (CRQ) was sent to a randomly chosen sample of 150 CGCA members, their administrators, and their clients. Counsellors were asked to respond to the CRQ both in terms of what they were doing and in terms of what they judged they should be doing. Returns were received from 49 CGCA members, 24 clients, and 27 administrators, representing all provinces and most categories of membership in the Association. The bulk of the respondents were employed in educational institutions, and were professionally well prepared. The most frequently reported counsellor activities were in the traditionally accepted areas of educational-vocational counselling. Most counsellors expressed a desire for a greater level of involvement in group counselling, research, and public relations activities. Counsellors were satisfied with their level of involvement on only approximately one quarter of the CRQ items. Comparison of counsellor, administrator, and client responses indicated that there is conflict or lack of consensus regarding counsellor role. It was found that counsellors and administrators had the least number of interposition differences, whereas administrators and clients had most.